问题 解答题
用递等式计算(能简算得就要简算)
3
4
×
2
5
+
3
5
×
3
4
1
4
+
5
14
+
3
4
)÷
1
7
6.5×6+3.5×6-35
1
7
8
×
5
9
+
5
9
×0.125-
5
9
0.35÷[(
5
6
-
2
3
)×3]
2
3
÷(
2
3
+
1
5
)÷
1
13
-10.
答案

(1)

3
4
×
2
5
+
3
5
×
3
4

=(

2
5
+
3
5
)×
3
4

=1×

3
4

=

3
4

(2)(

1
4
+
5
14
+
3
4
)÷
1
7

=(

1
4
+
3
4
+
5
14
)×7,

=(1+

5
14
)×7,

=1×7+

5
14
×7+,

=7+

5
2

=9

1
2

(3)6.5×6+3.5×6-35,

=(6.5+3.5)×6-35,

=10×6-35,

=60-35,

=25;

(4)1

7
8
×
5
9
+
5
9
×0.125-
5
9

=(1

7
8
+0.125-1)×
5
9

=(2-1)×

5
9

=1×

5
9

=

5
9

(5)0.35÷[(

5
6
-
2
3
)×3],

=0.35÷[

1
6
×3],

=0.35÷

1
2

=0.7,

(6)

2
3
÷(
2
3
+
1
5
)÷
1
13
-10,

=

2
3
÷
13
15
÷
1
13
-10,

=

10
13
÷
1
13
-10,

=10-10,

=0.

判断题
判断题